Análise do repertório de anticorpos de cavalo - Carlena Tahina Navasde Reyes (2022)
In 1901, the first Nobel Prize in medicine was awarded for investigating immune serum against tetanus toxin produced by immunized horses. After that, polyclonal horse antibodies were produced and used for treating and prophylaxis diphtheria, tuberculosis, tetanus, and pneumonia. Today, in Brazil, it represents the specific treatment for spider accidents of the genus Loxosceles, and in some countries, it has even been used as a treatment for SARS-CoV- 2. More than 120 years have passed since the horse was first used to produce antibodies against different diseases. However, very little is known about the adaptive immune system of this species, especially at the molecular level. For that reason, we characterize horses' heavy chain repertoire (IGH) from non-immunized, and Loxosceles spider immunized horses using HTS technology. In the non-immunized horses, we obtained an average of 248,169 IgM clones and 66,141 unique IgG clones from four domestic adult horses. Although the horse uses all the functional gene segments of the IGHV, about 80% of its antibodies use only three gene segments, and about 55% use only one gene segment of the IGHJ. This limited diversity of VJ appears to be offset by the junctional diversity of these antibodies. In this study, it was seen that junctional diversity in horse antibodies is very frequent, present in more than 90% of horse antibodies. Furthermore, the length of this region appears to be longer in horse antibodies than in antibodies from other species. The addition of N1 and N2 nucleotides ranges from 0 to 111 nucleotides. This diversity mechanism may be one of the most important in providing variability to the equine antibody repertoire. In the case of immunized horses, we have found an average of 114,933 clones for IgG, with coverage determined by the rarefaction of 80%. Using the clones from the repertoires before, after immunization, and those expanded, we observed similar characteristics among them, except for the use of three IGHV gene segments and a lower hydrophobicity in the CDR-H3 region in the expanded clones. This study points out the need to characterize the molecules involved in the generation of equine antibody diversity, such as TdT, to better understand the characteristics of the horse antibody repertoire. In summary, our analyzes provide new insights on horse antibody composition, generation of diversity, and particularities compared to other species, such as frequency and length, and addition of N nucleotides, and may apply to the rational design of synthetic antibodies intended for therapeutic use.